Behavior of reverse top-seat angle connection at ambient and elevated temperatures / Leong Siong Hean - Leong, Siong Hean (2017)
Steel tubular column members have been widely adopted in construction industry due to its numerous advantages. However, the closed-section profile characteristics of tubular columns severely limit the connection possibilities. Welding method is acceptable but discouraged because of on-site issues. Bolted connections are preferable because of its simplicity, economical and easy assembly. A combination of both welding and bolting is the compromise between benefits and disadvantages. Therefore, a new bolted connection of open beam sections to tubular column that consists of welded angles and end plate, called reverse top-seat angle connection is proposed and investigated. This study focuses on experimental and numerical methods of examining the behavior of reverse top-seat angle connection at ambient and elevated temperature. Three specimens were tested at ambient temperature with monotonic loading while four specimens were tested at elevated temperature according to ISO834 heating curve under anisothermal conditions with static load. The results from tests in both conditions provide the validation data for finite element models developed in ABAQUS. Only half of the specimen is modelled and uses solid hexahedral brick elements. Contacts and pretension are included into the model for closer representation of the experimental tests while the temperatures are considered as static step in the model. For ambient models, the validated model was used in parametric studies on the geometrical details that may affect the connection behavior, including the angle thickness, plate thickness, leg length, stiffener and gauge length. Several parameters have been identified to provide a critical contribution to the connection behavior. Results from the elevated temperature tests show the difference in deformation of the connection due to the effects of higher temperature and the boundary conditions for both test conditions. In terms of connection performance under elevated temperatures, two configurations of the connections are discovered to remain ductile under the temperature of 700C while the other two specimens developed earlier failures. Effects of axial loadings, isothermal conditions and the effect of boundary conditions were studied as the variation under elevated temperatures. The results have shown that the connection is both practical and has comparable performance to other connection types to tubular columns with flexible modification options. The connection can be considered for future studies, considering the various additional components that could be added to the connection to increase the performance accordingly.